Study of charmless hadronic B meson decays to pseudoscalar-vector final states. - Jessop, C; Marsiske, H; Perl, M; Savinov, V; Ugolini, D; Zhou, X; Coan, T; Fadeyev, V; Maravin, Y; Narsky, I; Stroynowski, R; Ye, J; et al. (American Inst of Physics, 2000)
We report results of searches for charmless hadronic B meson decays to pseudoscalar( pi(+/-), K+/-, pi(0), or K(0)(S))-vector( rho, K(*), or omega) final states. By using 9.7x10(6) BB pairs collected with the CLEO detector, we report the first observation of B(-)--->pi(-)rho(0), B(0)-->pi(+/-)rho(-/+), and B(-)-->pi(-)omega, which are expected to be dominated by hadronic b-->u transitions. The measured branching fractions are (10.4(+3.3)(-3.4)+/-2.1)x10(-6), (27.6(+8.4)(-7.4)+/-4.2)x10(-6), and (11.3(+3.3)(-2.9)+/-1. 4)x10(-6), respectively. Branching fraction upper limits are set for all of the other decay modes investigated.